Design and development of a remotely operated vehicle with new maneuvering method - Zainah, Md. Zain; Maziyah, Mat Noh; Khairil Ashraff, Ab Rahim; Nurfadzillah, Harun (NISCAIR PUBLICATIONS, 2017)
In this paper, a remotely operated vehicle (ROV) consisting of four thrusters is designed and developed called X4-ROV. X4-ROV is a micro observation class ROV to be used mainly for visual observation of underwater structure or environment by utilizing a high definition web camera. The designed vehicle structure was aims towards portability and maneuverability in attitude motions of roll, pitch, and yaw, and the translational motion forward/reverse/lateral. This work explains the use and modification of an open-source platform (OpenROV) into X4-ROV system.